Becoming IELTS Examiners: Demystifying Native-Speakerism in the Area of English Language Testing - Pritz Hutabarat (Journal of Education and Teaching (JET), 2023)
The field of English language teaching (ELT) has long been a fertile soil for native-speakerism where the native English teachers (NESTs) enjoy the privilege to be crowned as the ideal teachers of the language.  Such belief is ingrained in all aspects of ELT including English language testing such as in International English language Testing System (IELTS), where the presence of non-native English examiners is extremely rare. Departing from this phenomenon, this study, conducted as a narrative case study, embarked to counter such claim by looking into the professional credentials and experiences of three non-native English teachers (NNESTs) who, against all odds, become official IELTS examiners in Indonesia. The data of the study were gathered through interviews and analyzed using thematic analysis. The findings show that the participants develop native-like level of fluency as the result of their investment in developing English skills through engaging in English mediated communication, interactions and learning in private English language institutions (PELIs). Moreover, their success is also attributed to their international teaching certificates which opened doors for them to compete with NESTs. Thus, this study seeks to inspire NNESTs to continuously develop their teaching credentials and to boost their confidence as legitimate teachers of English.